PROGNOSIS OF INHALATION INJURY MORTALITY RATE WITH REVISED BAUX SCORE AT DR. SOETOMO GENERAL ACADEMIC HOSPITAL, SURABAYA, INDONESIA (2019-2021) - Salsabilla, Dhea Hasna; Agus Santoso Budi; Diah Mira Indramaya; Muslim, Ronaldo (Universitas Airlangga, 2024)
Highlights: Fire is the most frequent cause of burns, while thermal contact is the least common. Mortality rate with revised Baux score in burn patients with inhalation injury showed a significant relationship. Abstract: Introduction: Burn trauma has quite a high mortality rate in Indonesia. One of the scoring systems that is straightforward to apply is the revised Baux score. However, there is no standardised scoring system that is currently in use in our institution. Therefore, the purpose is to determine the feasibility of using this scoring system in our population's features. Methods: This research is a retrospective study with research design case control design using secondary data in the form of medical record data from patients with acute burn trauma that were admitted to Burn Unit of Dr. Soetomo General Academic Hospital in Surabaya between January 2019 and December 2021. All the data will be divided by their group and analysed with SPSS software. Results: The study found significant relationships between several factors and mortality rates among burn patients. Age, total burn surface area percentage, presence of inhalation injury, and the revised Baux Score all showed significant correlations with mortality rate (p < 0.005). Specifically, among burn patients with inhalation injury, the correlation between mortality rate and revised Baux score remained significant (p=0.002). Conclusions:The study revealed that age, the percentage of total burn surface area, and the presence of inhalation injury are significantly associated with mortality rate among burn patients. Additionally, the revised Baux Score was identified as a useful tool for predicting the prognosis of burn patients with inhalation injury. These findings emphasize the importance of these factors in assessing and managing outcomes for burn patients, particularly those with inhalation injury.